Saturn's Northern Aurorae at Solstice From HST Observations Coordinated With Cassini's Grand Finale. Issue 18 (23rd September 2018) - Lamy, L.; Prangé, R.; Tao, C.; Kim, T.; Badman, S. V.; Zarka, P.; Cecconi, B.; Kurth, W. S.; Pryor, W.; Bunce, E.; Radioti, A.
Abstract: Throughout 2017, the Hubble Space Telescope (HST) observed the northern far‐ultraviolet aurorae of Saturn at northern solstice, during the Cassini Grand Finale. These conditions provided a complete viewing of the northern auroral region from Earth and a maximal solar illumination, expected to maximize the ionosphere‐magnetosphere coupling. We analyze 24 HST images concurrently with Cassini measurements of Saturn's kilometric radiation and solar wind parameters predicted by two magnetohydrodynamic models. The aurorae reveal highly variable components, down to timescales of minutes, radiating 7 to 124 GW. They include a nightside‐shifted main oval, unexpectedly frequent and bright cusp emissions, and a dayside low‐latitude component. On average, these emissions display a strong local time dependence with two maxima at dawn and premidnight, the latter being newly observed and attributed to nightside injections possibly associated with solstice conditions. These results provide a reference frame to analyze Cassini in situ measurements, whether simultaneous or not. Plain Language Summary: In 2017, the Hubble Space Telescope regularly observed the northern ultraviolet aurorae of Saturn in coordination with Cassini in situ measurements obtained during the Grand Finale, when the spacecraft flew across magnetic field lines connected to the aurorae. Hubble imaged Saturn's aurorae at 24 occasions spread over 7 months during northern solstice, when the northern auroral region was both fully visible from Earth and permanently illuminated by the Sun. The observed aurorae display a variety of components observed poleward of 68° latitude with different properties, some of which were unreported before. These emissions strongly vary with time, down to a few minutes, and radiate from 7 to 124 GW. On average, the auroral intensity also strongly varies with local time (a Sun‐referenced frame) and peaks at dawn, as previously observed, and also premidnight, pointing to a recurrent nightside activity of the magnetosphere. These results provide a reference basis to analyze Cassini in situ measurements. Key Points: Saturn's northern UV aurorae at solstice were sampled from HST observations coordinated with Cassini's Grand Finale The observed aurorae are highly variable with powerful events, radiating up to 124 GW, controlled by solar wind and planetary rotation The average auroral brightness strongly varies with LT with two maxima at dawn (previously known) and premidnight (newly identified)